Dead post society - Kelly, Diane (Kelly, Diane. House-flipper mystery, 2025)
Carpenter Whitney Whitaker and her cousin Buck are no strangers to murder. After all, they've encountered corpses on their properties before. But this is the first time they decided to take a chance on a property where two suspicious deaths have already occurred. Most buildings on the former boarding school property will be repurposed for an upscale retirement community, but the developer has no use for the headmaster's house given its violent history. The headmaster and his wife were killed there decades earlier, their deaths remaining unsolved to this day. Still, it seems a shame to see the beautiful Victorian give way to decay or the wrecking ball, even if many claim the unsettled souls of the victims still wander its halls, seeking retribution and justice. Can Whitney and Buck exorcise the structure's demons, solve the cold case, and give the building new life? Or will ghosts from the past seek to silence them forever?--